Ethical Implications of Chatgpt in Higher Education: a Systematic Review - Mbotho, Amber; Mabina, Alton (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This systematic review examines the ethical implications of ChatGPT in higher education, focusing on issues such as academic integrity, responsible AI use, and its impact on learning outcomes. A structured search of five major databases, following PRISMA methodology, identified 696 records, of which 44 studies met the inclusion criteria. The findings reveal that ChatGPT, while a powerful educational tool, raises significant concerns about plagiarism, reduced critical thinking, and uneven adoption across regions. Studies demonstrate that ChatGPT can enhance learning when used as a supplementary resource but poses risks when relied upon excessively. The review highlights gaps in current research, particularly the lack of longitudinal studies and limited evidence on regional variations in adoption. Limitations of the review process, such as the exclusion of gray literature and potential biases in self-reported data, are acknowledged. Despite these limitations, the review offers actionable insights, emphasizing the need for robust ethical guidelines, enhanced plagiarism detection systems, and educator training to promote responsible AI use. This paper contributes to the ongoing discourse on integrating AI in education by addressing its benefits and challenges. It calls for future research to explore long-term impacts and practical frameworks for ethical AI adoption, ensuring ChatGPT serves as a complementary tool rather than a disruptive force in higher education